Domesticated Capitalism? (KULT_online, 2017)
In Markt und Gewalt. Die Funktionsweise des historischen Kapitalismus Heide Gerstenberger challenges the theoretical assumption that capitalism tends toward self-domestication. She argues that direct violence neither contradicts economic rationality, nor does the dynamic of capitalist economy call for abandoning violence. On the contrary, equity owners most likely would exploit any opportunity to maximize their profit, if they weren’t challenged by governmental policies and public opinions. Providing a rich historical overview from the pre-capitalist world trade of the 15th century to the industrialization of the 19th century and present-day global economy, Gerstenberger describes the individual impact of direct violence on people over the course of time primarily as resulting from political struggles.